ALIH KODE CAMPUR KODE DALAM FILM “PR-KU MUNG KOWE” DI YOUTUBE BATS CHANNEL - Ritasari, Siska Dina; Firnanda, Reyza (Universitas Negeri Surabaya, 2024)
Language variations are often found in people's daily conversations. Language variation arises when a society has diverse languages. Language variation is a variation or variety of language according to its use. In language variations discussing code switching and code mixing, code switching is the event of using one code to another. There are two forms, namely internal (inner) code switching and external (outer) code switching. Meanwhile, code mixing is the process of inserting regional languages or other foreign languages. There are two forms, namely positive and negative code mixing. Data and data sources are from the film